Management of Sex Offenders by Probation and Parole Agencies in the United States, 1994 - English, Kim ([Verlag nicht ermittelbar], 1996)
This study examined various ways states approach and sanction sex crimes (i.e., child sexual abuse, incest, and sexual assault) and sex offenders. The aim of the study was to obtain basic information about policies and procedures of probation and parole agencies with respect to adult sex offender case management. State corrections administrators in 49 states and the District of Columbia were contacted to supply information on their states' probation and parole offices and the corresponding jurisdictions. From these offices, probation and parole supervisors at the office-management level were selected as survey respondents because of their familiarity with the day-to-day office operations. Respondents were asked about the usage of various supervision methods, such as electronic monitoring, requiring offenders on probation or parole to register with law enforcement agencies, and polygraph testing. Sanctions such as requiring the offenders to seek treatment and forbidding contact with the victim were discussed, as were various queries about the handling of the victim in the case (whether a written statement by the victim was routinely included in the offender's file, whether officers usually had contact with the victim, and whether there was a system for advising victims of status changes for the offender). Other questions focused on whether the office used specialized assessments, caseloads, programs, and policies for sex offenders that differed from those used for other offenders. Various issues regarding treatment for offenders were also examined: who chooses and pays the treatment provider, whether the agency or the court approves treatment providers, what criteria are involved in approval, and whether the office had an in-house sex offender treatment program.